The Influence of Internet Availability, Connectivity with Financial Applications, and The Skill to Understand Fintech on The Success of Fintech Users for Visitors at Mie Gacoan SMEs in Tlogomas, Malang City - Neca; Cakti Indra Gunawan; R Y Susanto (IRDH International Journal of Social Sciences & Humanities, 2026)
The aim of this study is to determine and understand how internet availability, connectivity with financial applications, and skills in understanding fintech affect success in using fintech. One dependent variable and three independent variables are used in the quantitative research design. The dependent variable is fintech user success (Y) and the independent variables are internet availability (X1), connectivity with financial applications (X2), and skills in understanding fintech (X3). The total number of respondents was 100 individuals who had previously purchased or visited Mie Gacoan Tlogomas in Malang City. In this study, the data analysis method used was multiple linear regression analysis. Based on the results of the study, internet availability, connectivity with financial applications, and skills in understanding fintech influence the success of fintech users.